Preparation of ZnO Thin Films by Galvanostatic Method - Wu, Shibiao; Xu, Ling; Xu, Haiyan; Chen, Xia; Ge, Yejun; Zhu, Shaofeng (Asian Journal of Chemistry, 2012)
Zinc oxide films were electrodeposited on ITO glass from aqueous solution containing 0.2 mol/L zinc nitrate using galvanostatic method. The morphology was characterized by scanning electron microscopy. The structure of the films was investigated with XRD method. The electrodeposition process conditions are followings: electric cell temperature is 60 ºC; current density is 5-10 mA/cm2.